2021
DOI: 10.1097/nne.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Global Nursing Hackathon Experience

Abstract: Background: Hackathons are organized to bring together both experienced and novice individuals from a variety of backgrounds to brainstorm creative solutions to complex issues. Hackathons may last from a few hours to a few days and may provide rewards for winning entries. Purpose: In this article, we describe an experience with a scientific hackathon at an international nursing research congress in Calgary, Canada. We discuss the purpose, process, benefits, and challenges of this hackathon. Approach: For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 41 studies (98%) reported the number of designathon participants 7 8 18–53 55–57. The median number of individuals participating in designathons was 49 (IQR 34–90, range 6–434), and the median number of teams was 8 (IQR 5–14.5, range 2–40).…”
Section: Resultsmentioning
confidence: 99%
“…As revealed by the conceptual structure of the dataset, health and medicine disciplines are also starting to leverage hackathons (e.g., Butt et al, 2021 ; Mevawala et al, 2021 ). More than half (24/41) of the publications in this academic discipline were published from 2020–2022 during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, however, the NGNR team opted to revisit community outreach planning with a diverse group of nursing professional development practitioners, using the hackathon approach (see What Is a Hackathon? [1][2][3][4] ).…”
Section: Defining the Problemmentioning
confidence: 99%
“…The approach can leverage collaboration, creativity, and speed to create new approaches to optimize health care. 2 By the end of the event (which can range from hours to days), all participants will ideally have designed a viable product for consideration.…”
Section: What Is a Hackathon?mentioning
confidence: 99%